Effect of jackfruit seed fortification on high calcium milk on bone collagen density - Aulia Ayub; Fun Nagede Adinsyah; Arum Trisnaningtyas Sugiyanto Putri; Presty Dwi Fitriani; Risma Martasuri; Tetiana Haniastuti (Majalah Kedokteran Gigi Indonesia, 2018)
Osteoporosis is a bone disease characterized by reduced bone mass and damage to the microarchitecture of bone tissue. One of osteoporosis types is primary type-1 osteoporosis or postmenopausal osteoporosis due to estrogen deficiency. Calcium is an important mineral that plays a central role in the formation of bone strength structure. Jackfruit seeds (Artocarpus heterophyllus) contain isoflavones that can replace the role of estrogen in the body. Fortification of jackfruit seeds and high calcium milk can be a potential alternative for the treatment of postmenopausal osteoporosis. The purpose of this study was to determine the effect of drinking high calcium milk fortified with jackfruit seed extract (Artocarpus heterophyllus) on alveolar bone collagen fiber density of menopause induced rats. Twenty-five Sprague dawley rats were included in this study. Twenty Sprague dawley rats were ovariectomized, while 5 rats were left untreated (normal control group). Seven days after ovariectomy was performed, 5 rats were treated with fortification of jackfruit seed extract and high calcium milk, 5 rats were treated with jackfruit seed extract, 5 rats were treated with high calcium milk, and 5 rats were left untreated (ovariectomized control group). The treatments were done for 28 days. The rats were euthanized and the alveolar bone was taken and processed for a histological specimen. Alveolar bone collagen fibers were observed under a binocular microscope with 100 magnification. Kruskal-Wallis result showed there was a significant difference in the alveolar bone collagen fiber density among these groups (p<0.05). Mann-Whitney U Test showed a significant difference (p<0.05) in the alveolar bone collagen fiber density of the rats treated with fortification of jackfruit seed extract and high calcium milk compared to the group treated with jackfruit seed extract, that with high calcium milk, or ovariectomized control group. No significant difference in alveolar bone collagen fiber density was found between the group treated with fortification of jackfruit seed extract and high calcium milk and the normal control group (p>0.05). In conclusion, consuming high calcium milk fortified with jackfruit seed extract increases the density of alveolar bone collagen fibers.